CLINICAL OBSERVATIONS OF COMPLICATIONS AFTER BCG-M VACCINATION - V. M. Kolomiets; L. V. Kovylyanskaya; N. M. Bryntseva (Туберкулез и болезни лёгких)
2 cases of BCG ostitis, developing in 2-4 years after vaccination with BCG-M were followed up. Potential risk factors of their developing could be subinfections and traumas.